GENERAL ELECTIONS AS AN EMBODIMENT OF THE POLITICAL RIGHTS OF CITIZENS - Syaiful Asmi Hasibuan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to analyze general elections as a manifestation of the political rights of citizens. General elections, as part of democracy, bring a lot of hope for the development and progress of democracy. The concept of democracy in general must emphasize the sovereign power of the people in the concept of democracy as the highest authority. Democracy requires public participation in evaluating policies that will determine people's lives in the future. In short, a democratic country is a country that is organized on the basis of the will and will of the people. General elections as part of the means of fulfilling the demands of democracy and provide the widest possible opportunity for the people to participate actively and directly in policy making by exercising their right to choose the leader they want. Therefore, in relation to the implementation of citizens' human rights, the government needs to guarantee the holding of regularly scheduled general elections. In accordance with the principle of people's sovereignty, where the people are sovereign, all aspects related to the holding of general elections must also be returned to the people to decide.